POTENSI PENGEMBANGAN TERNAK SAPI PADA USAHA TANI DIKECAMATAN TARERAN MINAHASA - Mirah, Riko E.; Endoh, E. K.M; Pandey, J.; Salendu, A. H.S (Universitas Sam Ratulangi, 2015)
POTENSIAL DEVELOPMENT OF CATTLE IN TARERAN SUB DISTYRICT, MINAHASA.Farm development showed a good prospect and has an important role in the growth of the agricultural economy . The problem is the extent to which the potential of land resources , human resorces and livestock capacity . Based on this problems we performed the research / The aimed of the research was to know potensial development of cattle in District Tareran South Minahasa regency Survey mehode was used . Source of data used are primary data and secondary data . Primary data was collected from the district office and the Office Tareran BP3K ( Hall extension , agriculture , fisheries and forestry ) .Secondary data collected from government office that in line with this research.Â Datal analysis used descriptive analysis , and analysis of the potential for livestock development efektif.Hasil bahwapotensi study showed maximum in livestock units based land resources ( PMSL ) of 5.238,1ST . Capacity increase in the cattle population by land resources ( KKPTR ( SL ) of 5058.65 ST , the real population of cattle ( POPRIL ) of 179,45ST , Potential of maximum based head of the family ( PMKK ) for 7380 ST , and capacity enhancement cattle population ( KPPTR ( KK ) of 7200.55 ST .. Â Keywords : cattle , potential , development